Analysis of clinical features of oxcarbazepine-induced Stevens-Johnson syndrome and toxic epidermal necrolysis - Yan, Qingzi; Liu, Xiang; Lei, Haibo; Liu, Renzhu; Hu, Yixiang (Frontiers in Medicine, 2023)
Background: Stevens-Johnson syndrome (SJS) is considered a hypersensitivity syndrome affecting the skin and mucous membranes. It has been reported that an anticonvulsant drug, oxcarbazepine, may cause Stevens-Johnson syndrome and toxic epidermal necrolysis (TEN). However, the clinical features of oxcarbazepine-induced Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) remain ambiguous. This article aims to explore the clinical features of SJS/TEN. Methods: Systematic searches of several Chinese and English databases were conducted for case reports published on PubMed, EMBASE, Web of Science,